Turn-taking in conversation uttered by Madurese community in Jember - Bambang Wibisono; Akhmad Haryono (UNIB Press, 2022)
Turn-taking in conversation is unique in the Madurese ethnic culture. This study aims to describe the turn-taking in conversation that applies to the Madurese community in Jember. To achieve this goal, a qualitative approach was used. Data were obtained through participatory observation with record and note techniques, then analyzed descriptive qualitative. The results showed that there were at least two speech shift patterns demonstrated by the Madurese community in Jember, namely, informal verbal communication and formal verbal communication. In informal verbal communication, two patterns were found, namely: (1) overlapping turn-taking in conversation patterns, and (2) turn-taking in conversation patterns without overlapping speech. In formal communication, the turn-taking pattern is always shown without overlapping speech. Interrupting people's speech in situations of formal verbal communication is considered to violate prevailing rules and is subject to negative stigma from society. The results of this study will have implications for the implementation of the use of honorifics in communication in Tapal Kuda area involving speech participants from different social statuses, roles, positions, and ages.